Mid-Ocean Ridge and Storm Enhanced Mixing in the Central South Atlantic Thermocline - Wei, Jingxuan; Gunn, Kathryn L.; Reece, Robert (Frontiers in Marine Science, 2022)
We investigate the spatial distribution of diapycnal mixing and its drivers in the central South Atlantic thermocline between the Rio-Grande Rise to the Mid-Atlantic Ridge. Diapycnal mixing in the ocean interior influences the slowly evolving meridional circulation, yet there are little observations of its variability with space and time or its drivers. To overcome this gap, seismic reflection data are spectrally analyzed to produce a 1600 km long full-thermocline vertical section of diapycnal diffusivity, that has vertical and horizontal resolution of O(10) m and spans a period of 4 weeks. We compare seismic-derived mixing rates with CTD-derived diffusivities and direct observations from 1996, 2003, and 2011. In the mean and on decadal scales, we find that thermocline diffusivities have changed little in this region, retaining a background value of 1  10-5 m2 s-1. Imprinted upon the background rates, mixing is heterogeneous at mesoscales. Enhanced mixing, exceeding 10  10-5 m2 s-1 and spreading between 200 and 700 m depth, is found above the Mid-Atlantic Ridge suggesting the ridge enhances diffusivity by at least one order of magnitude across the entire water column. Rapid decay of diffusivities within 30 km of the ridge implies local dissipation of tidal energy. Above smooth topography, patches of enhanced mixing are possibly caused by a recent storm that injects near-inertial energy into the water column and elevates mixing from 3  10-5 m2 s-1 to 50  10-5 m2 s-1 down to depths of more than 600 m. The propagation speed of near-inertial energy varies substantially from 17 to 27 m/day. Faster speed, and therefore greater penetration depths of 800 m, are probably facilitated by an eddy. Together, these data extend the observational record of central South Atlantic thermocline mixing and provide insights into drivers of mesoscale variability.